2022
DOI: 10.1093/oncolo/oyac108
|View full text |Cite
|
Sign up to set email alerts
|

Moderate Colitis Not Requiring Intravenous Steroids Is Associated with Improved Survival in Stage IV Melanoma after Anti-CTLA4 Monotherapy, But Not Combination Therapy

Abstract: Background For patients with melanoma, gastrointestinal immune-related adverse events are common after receipt of anti-CTLA4 therapy. These present difficult decision points regarding whether to discontinue therapy. Detailing the situations in which colitis might predict for improved survival and how this is affected by discontinuation or resumption of therapy can help guide clinical decision-making. Materials and Methods Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…GO biological process enrichment analysis revealed that TXYF in the treatment of UC may be related to biological processes such as endotoxin response, regulation of small molecule metabolism, regulation of reactive oxygen species metabolism, regulation of apoptosis signaling pathways, and negative regulation of cell proliferation. Excessive activation of oxidative stress (OS) can cause excessive production of free radicals, leading to lipid and protein peroxidation, which in turn leads to damage to the intestinal mucosal protective barrier and leads to the onset of UC [ 35 , 36 ]. Our molecular docking results showed that the binding energies of naringin and MAPK, as well as albiflorin and SRC, were -8.5 and -6.4 (kcal/mol), respectively, both less than -5.0, indicating strong binding activity between the drug and the target.…”
Section: Discussionmentioning
confidence: 99%
“…GO biological process enrichment analysis revealed that TXYF in the treatment of UC may be related to biological processes such as endotoxin response, regulation of small molecule metabolism, regulation of reactive oxygen species metabolism, regulation of apoptosis signaling pathways, and negative regulation of cell proliferation. Excessive activation of oxidative stress (OS) can cause excessive production of free radicals, leading to lipid and protein peroxidation, which in turn leads to damage to the intestinal mucosal protective barrier and leads to the onset of UC [ 35 , 36 ]. Our molecular docking results showed that the binding energies of naringin and MAPK, as well as albiflorin and SRC, were -8.5 and -6.4 (kcal/mol), respectively, both less than -5.0, indicating strong binding activity between the drug and the target.…”
Section: Discussionmentioning
confidence: 99%
“…Moderate colitis which does not require the use of intravenous steroids is consistent with an improved overall survival of patients with stage IV melanoma when treated with a single anti-CTLA-4 drug, but not with combination drugs. This holds true even after the completion of therapy (159). Multiple nonrandomized studies have shown excellent results in patients who discontinue treatment after being treated for 1-2 years and disease progression is also uncommon in the following 2-5 years of treatment termination (160)(161)(162).…”
Section: Factors Affecting Drug Usementioning
confidence: 99%